Physical Modelling of Roll and Pitch Motions of Travelling or Stationary Ship in Large-Scale Landslide-Generated Waves - Pei-yin Yuan; Ping-yi Wang; Yu Zhao (Advances in Civil Engineering)
Large-scale landslides often occur in river-type reservoirs, and landslide-generated waves affect navigation channels and the navigation of ships. Thus, such waves cause widespread regional disasters. This study establishes a mechanical model of landslide-generated waves via field investigations and data collection, reveals the mechanism and process of landslide-generated waves, and investigates the propagation characteristics of landslide-generated waves along a sloping wave. The feasibility of the model is verified via (i) regularity analysis, (ii) comparative analysis of the effect of landslide-generated waves of mountain river channel reservoirs on the movement characteristics of navigation vessels and stationary vessels, (iii) deviation from the equilibrium position, and (iv) an in-depth study of the influence of large-scale landslide-generated waves on ships in different navigation positions in a river channel. Countermeasures are proposed for a sailing ship to tackle a sudden landslide-generated wave; these measures can provide a theoretical basis for ships to sail safely through large-scale landslide-generated waves.